2015
DOI: 10.1186/s13098-015-0013-8
|View full text |Cite
|
Sign up to set email alerts
|

Association between maternal glucose levels during pregnancy and gestational diabetes mellitus: an analytical cross-sectional study

Abstract: BackgroundTo evaluate the association between fasting glucose levels in women throughout pregnancy and the occurrence of gestational diabetes mellitus (GDM) and other pregnancy complications, macrosomia, and cesarean delivery.MethodsAn analytical cross-sectional study with 829 healthy pregnant women receiving health care at a public maternity unit in Rio de Janeiro between 1999 and 2008. The dependent variables assessed in the study were: GDM (was confirmed when two or more values were above the glucose curve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 19 publications
0
15
0
1
Order By: Relevance
“…Even minor elevations of glucose in pregnancy are associated with worse fetal and maternal outcomes. Seabra et al [ 25 ] performed a cross-sectional study of 829 healthy pregnant women and found that second and third trimester FPG levels below the cut-off values for a diagnosis of GDM were associated with an increased risk of pregnancy complications. In the current study, FPG provided a better diagnostic value than GA or HbA1c only at 24–28 weeks’ gestation.…”
Section: Discussionmentioning
confidence: 99%
“…Even minor elevations of glucose in pregnancy are associated with worse fetal and maternal outcomes. Seabra et al [ 25 ] performed a cross-sectional study of 829 healthy pregnant women and found that second and third trimester FPG levels below the cut-off values for a diagnosis of GDM were associated with an increased risk of pregnancy complications. In the current study, FPG provided a better diagnostic value than GA or HbA1c only at 24–28 weeks’ gestation.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been well documented in several studies 4 7 , 11 , 13 that CS delivery is more associated with increased fetal complications including reduced Apgar score, respiratory distress syndrome, and neonatal transfer rate. Consistent with other studies, 10 the risk of birth asphyxia among babies born by CS was higher than those delivered vaginally.…”
Section: Discussionmentioning
confidence: 99%
“… 6 8 Other surveys benefit vaginal delivery because cesarean delivery has a higher risk of maternal death, 9 a longer recovery time and operative complications, 10 a higher risk of unexplained stillbirths in subsequent pregnancies, 6 and respiratory problems of the newborn infant. 11 13 …”
Section: Introductionmentioning
confidence: 99%
“…The International Association of Diabetes Pregnancy Study Group (IADPSG) for the diagnosis of GDM also called the 2013 WHO criteria for GDM proposed that Pregnant women with fasting plasma glucose greater than or equal to 5.1 mmol/l (92 mg/dl) but less than 7.0 mmol/l (126 mg/dl) may be diagnostic of GDM [40]. Seabra et al, observed that second and thirdtrimester fasting glucose levels of 4.47 to 5.20mmol/l were associated with an increased risk of pregnancy complications; GDM, macrosomia and cesarean section deliveries [41]. Seabra et al, concluded that the gestational periods in which maternal blood glucose had a greater influence on the appearance of complications were the second and third quarters, indicating vulnerable periods since they arerelated to intensive developmental phase and fetal growth [41].…”
Section: Discussionmentioning
confidence: 99%
“…Seabra et al, observed that second and thirdtrimester fasting glucose levels of 4.47 to 5.20mmol/l were associated with an increased risk of pregnancy complications; GDM, macrosomia and cesarean section deliveries [41]. Seabra et al, concluded that the gestational periods in which maternal blood glucose had a greater influence on the appearance of complications were the second and third quarters, indicating vulnerable periods since they arerelated to intensive developmental phase and fetal growth [41]. Hyperglycemia from any cause can seriously affect both mother and baby and could increase the risk of complications in pregnancy, labour and after delivery in conditions not monitored properly [42].…”
Section: Discussionmentioning
confidence: 99%